Assessment of scientific gaps related to the effective environmental management of deep-seabed mining. (April 2022) - Amon, Diva J.; Gollner, Sabine; Morato, Telmo; Smith, Craig R.; Chen, Chong; Christiansen, Sabine; Currie, Bronwen; Drazen, Jeffrey C.; Fukushima, Tomohiko; Gianni, Matthew; Gjerde, Kristina M.; Gooday, Andrew J.; et al.
Abstract: A comprehensive understanding of the deep-sea environment and mining's likely impacts is necessary to assess whether and under what conditions deep-seabed mining operations comply with the International Seabed Authority's obligations to prevent 'serious harm' and ensure the 'effective protection of the marine environment from harmful effects' in accordance with the United Nations Convention on the Law of the Sea. A synthesis of the peer-reviewed literature and consultations with deep-seabed mining stakeholders revealed that, despite an increase in deep-sea research, there are few categories of publicly available scientific knowledge comprehensive enough to enable evidence-based decision-making regarding environmental management, including whether to proceed with mining in regions where exploration contracts have been granted by the International Seabed Authority. Further information on deep-sea environmental baselines and mining impacts is critical for this emerging industry. Closing the scientific gaps related to deep-seabed mining is a monumental task that is essential to fulfilling the overarching obligation to prevent serious harm and ensure effective protection, and will require clear direction, substantial resources, and robust coordination and collaboration. Based on the information gathered, we propose a potential high-level road map of activities that could stimulate a much-needed discussion on the steps that should be taken to close key scientific gaps before any exploitation is considered. These steps include the definition of environmental goals and objectives, the establishment of an international research agenda to generate new deep-sea environmental, biological, and ecological information, and the synthesis of data that already exist.